2018
DOI: 10.1111/exd.13491
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the facial microbiome in twins discordant for rosacea

Abstract: Previously, we determined that genetic and environmental factors contributed equally towards rosacea in twins. To assess an environmental factor, we characterized the malar cheek bacterial microbiome from twins discordant for rosacea. We found no significant difference in facial microbiome alpha and beta diversity between related twins discordant for rosacea. However, the relative percentage abundance of Gordonia and Geobacillus, low-abundant genera, was positively and negatively associated with rosacea severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
4
25
3
Order By: Relevance
“…However, one should carefully interpret its increase as Weissella confusa has also been associated with sepsis and other serious infections in humans [36]. In fact, the abundance of Weissella genera showed positive correlation with rosacea severity in a twin study [27] (univariate random effect Poisson regression), which contradicts our findings.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However, one should carefully interpret its increase as Weissella confusa has also been associated with sepsis and other serious infections in humans [36]. In fact, the abundance of Weissella genera showed positive correlation with rosacea severity in a twin study [27] (univariate random effect Poisson regression), which contradicts our findings.…”
Section: Discussioncontrasting
confidence: 94%
“…Our longitudinal cohort study examined the skin microbiota of untreated patients and the influence of systemic antibiotics on the skin microbiota. Through 16s rRNA gene sequencing, we found S. epidermidis and C. acnes to be prevalent in the untreated rosacea skin samples, consistent with prior findings [27][28][29][30]. Present in healthy and diseased skin, their roles as commensals or opportunistic organisms are not completely understood.…”
Section: Discussionsupporting
confidence: 84%
“…Dysbiosis and decreased microbial biodiversity of the skin microbiome has been linked with many diseases, including acne, eczema [71], dermatitis [10], rosacea [72], Malassezia folliculitis [73], inflammation [74], psoriasis [75], general allergies [76], sunburn [77], athlete's foot & ringworm [78], wound healing [79], diabetic skin [51], leishmaniasis [49], blepharitis & conjunctivitis [80] and skin cancer [81].…”
Section: The Role Of Skin Microbiotamentioning
confidence: 99%
“…More recently, in a NRS-supported study in twins, Zaidi and colleagues [24] reported the first evidence highlighting the correlation between the severity of rosacea and microbial dysbiosis on the skin, but further study is needed to determine the species involved.…”
Section: Introductionmentioning
confidence: 99%